Engagement in physical activity, suicidal thoughts and suicide attempts among older people in five developing countries - Bishwajit Ghose; Ruoxi Wang; Shangfeng Tang; Sanni Yaya (PeerJ, 2019)
Background Suicide causes rising economic costs and public health risks for communities in the worldwide. Physical activity (PA) is considered a potentially feasible approach to reduce risk of suicide with low cost and high accessibility, and therefore attracting increasing attention. However, current literature on the association between PA and suicidal behavior amongst elderly people in low- and middle-income countries (LMICs) are scarce. Therefore, in this study we aimed to examine the relationship between suicidal thoughts (ST) and suicidal attempts (SA) with PA among elderly people in five LMICs. Methods Cross-sectional data were collected from WHO’s Study of Global Ageing and Adult Health (SAGE) with 2,861 participants aged 50 years or above. Variables included: self-reported occurrence of ST and SA during past 12 months and four types of PA (vigorous physical activity (VPA), moderate physical activity (MPA), walking/bike riding, moderate leisure time physical activity (MLPA)). Results The overall prevalence of taking >75 min of VPA/week, >150 min/week, MLPA and walking/bike riding were, respectively, 85.4% (95% CI [81.3–88.7]), 61.6% (95% CI [52.9–69.6]), 9.6% (95% CI [7.2–12.6]) and 75.1% (95% CI [68.7–80.6]). Respectively, 31.0% (95% CI [24.3–38.7]) and 5.5% (95% CI [3.9–7.5]) of the respondents reported having morbid thoughts and SA during last 12 months. In adjusted multivariable regression analysis, not engaging in PA revealed positive association with higher odds of having morbid thoughts and SA, however, with varying degrees for different types of PA among men and women and across countries. The adjusted odds ratio among elderly who encountered ST increased significantly with PA levels (1.265 in male and 1.509 in female with VPA, 1.292 in male and 1.449 in female with MPA, 1.669 in female with LMPA and 3.039 in women with walk/bike); similarly, with SA (1.526, 1.532, 1.474 and 1.392 in women with VPA, MPA, LMPA and Walk/bike, respectively). The degree of adjusted odds ratio varied between genders and among countries. Conclusion Although the data were cross-sectional, and no linear dose-response relationship was observed between PA and morbid thought and suicide ideation, the findings provide important indications of potential harmful effects of no/inadequate PA on psychological morbidities among older individuals. Promoting adequate PA among older individuals through community-based suicide prevention programs can potentially contribute to reduction in the burden of PA in LMICs.